A highly selective colorimetric chemosensor for detection of iodide ions in aqueous solution. Issue 89 (12th September 2016) - Chen, Jie; Lin, Qi; Li, Qiao; Li, Wen-Ting; Zhang, You-Ming; Wei, Tai-Bao
Abstract : A simple chemosensor can be used as a colorimetric sensor for the highly selective and sensitive detection of iodide anions in aqueous solution. Abstract : We synthesized a new iodide ion (I − ) chemosensor (CS ) based on a hydrazone derivative obtained from the condensation of 2-hydroxy-1-naphthaldehyde and 2, 4-dinitrophenylhydrazine. TheCS showed selective colorimetric recognition of I −, the miscellaneous competitive anions (F −, Cl −, Br −, HSO4 −, CH3 COO −, H2 PO4 −, SCN −, CN −, ClO4 − and S − ) did not lead to any significant interference. The detection limits of theCS for I − is 1.1 × 10 −6 M. The sensor has been successfully applied to estimate the content of iodide ions in urine. Moreover, ion test strips based onCS were fabricated, which could act as a convenient and efficient I − test kit for "in-the-field" measurement of iodide ions.